Method for pre-lithiating electrode by using lithium silicon alloy
By contacting the electrodes of the lithium-ion battery with LixSiy alloy particles in a specific range, the problem of large lithium loss in the anode material during the first cycle is solved, and higher stability and prelithiation efficiency are achieved, making it suitable for commercial production.
Patent Information
- Application Number
- CN202411911586.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2017-08-31
- Filing Date
- 2018-08-31
- Publication Date
- 2025-03-25
AI Technical Summary
In existing lithium-ion batteries, the loss of lithium in the anode material during the first cycle is large, and the use of lithium metal powder for prelithiation has problems such as safe treatment and reactivity that are difficult to adapt to commercial production.
Preliminization is performed by contacting the electrode with a plurality of LixSiy alloy particles, wherein at least 95% of the particle size is between 1 micron and 200 microns, and the lithium content in the LixSiy alloy is between 10% and 90% by weight.
It effectively prevents irreversible loss of lithium during the first charging/discharge cycle, improves the stability and prelithiation efficiency of the lithium-ion battery, and simplifies the processing and application process.
Smart Images

Figure CN119695052A_ABST
Abstract
Description
Background Art
[0001] Lithium-ion batteries are used in a variety of consumer electronics and are increasingly being adopted in electric vehicles. Researchers and developers are focusing on improving the performance of lithium-ion batteries for such applications. In this regard, anode materials such as graphite, silicon, silicon oxide, and graphite with silicon and / or silicon oxide are being used / tested. One problem associated with such anode materials is the loss of lithium during cycling. Since lithium loss is typically greater during the first cycle, lithium loss during the first cycle is of particular concern.
[0002] Pre-lithiation of anode materials can help compensate for lithium loss in lithium-ion batteries. To the best of the inventors' knowledge, fine lithium metal powder is the most commonly used commercially available pre-lithiation additive. However, there are several challenges in using lithium metal powder to pre-lithiate anodes, which hinder its application. For example, the inherent lightness of lithium metal powder and electrostatic forces between particles make it easily airborne and pose great challenges for safe handling and precise application and commissioning; and the high reactivity of lithium metal makes it difficult to adapt to commercial battery production lines.
[0003] Attempts have been made to address these challenges. For example, Zhao et al., in “Artificial Solid Electrolyte Interphase-Protected LixSiy Nanoparticles: An Efficient and Stable Prelithiation Reagent for Lithium-Ion Batteries”, state: “We recently demonstrated that LixSiy nanoparticles (NPs) synthesized by thermal alloying can serve as a high-capacity prelithiation reagent, although their chemical stability in the battery processing environment remained to be improved. Zhao et al. also stated, "Currently, the only commercial prelithiation reagent in powder for mis microscale stabilized lithium metal powder (SLMP) (FMC Lithium Corp.), which effectively compensates for the first-cycle irreversible capacity loss of different anode materials, such as SiO and Si-CNT composites."However, it is difficult to synthesize SLMP in research laboratories, and other practical challenges still remain to be addressed. "See J. Am. Chem. Soc., 2015, 137 (26), pp. 8372-8375. In the same publication, Zhao et al. proposed "a surface modification method to enhance the stability of LixSiy nanoparticles by exploiting the reduction of 1-fluorodecane on the LixSiy surface to form a continuous and dense coating...". However, applying this surface treatment technique in a commercial production environment would be expensive and tedious. In addition, the dense coating can reduce the performance of the Li-containing particles.
[0004]
[0006] Therefore, there is a need for new and improved methods of pre-lithiation of anodes, such as silicon-based anodes, particularly methods that will effectively prevent irreversible loss of lithium during the first charge / discharge cycle. Summary of the invention
[0005] The invention described herein satisfies the above needs by providing a method for pre-lithiation of an electrode, the method comprising contacting the electrode with a plurality of particles of one or more LixSiy alloys, wherein at least about 95% by volume of the particles have a size range of about 1 micron to about 200 microns, and each of the LixSiy alloys contains lithium in a content range of about 10% by weight to about 90% by weight. Also provided is such a method, wherein the lithium content of at least one of the LixSiy alloys ranges from about 10% by weight to about 70% by weight, or ranges from about 15% by weight to about 60% by weight, or ranges from about 40% by weight to about 50% by weight. Also provided is such a method, wherein the size range of two or more particles is about 1 micron to about 150 microns, or about 1 micron to about 70 microns, or about 1 micron to about 50 microns. Also provided is such a method, wherein at least one of the LixSiy alloys has been in contact with an organic substance. Also provided is such a method, wherein at least one of the LixSiy alloys has been in contact with an inorganic substance. Also provided is such a method, wherein the electrode is a graphite-based electrode or a silicon-based electrode. Also provided are methods wherein the prelithiation of the electrode is performed substantially in the absence of a solvent. Also provided are methods wherein the prelithiation of the electrode is performed in the presence of a solvent. Also provided are methods wherein the prelithiation of the electrode is performed on the surface of the electrode. Also provided are electrodes prelithiated according to the methods of the invention, and batteries comprising such electrodes, and such batteries wherein the electrodes are anodes, and such batteries wherein the anodes are adapted to release a greater amount of lithium when the battery undergoes a first charge / discharge cycle than would be released by an anode that has not been prelithiated according to the methods of the invention.
[0006] In addition, the invention described herein provides an electrode pre-lithiated according to the method described herein; and also provides a battery including such an electrode, which can be an anode or a cathode. In particular, a battery comprising an anode and a cathode is provided, wherein the anode has been pre-lithiated according to the method of the present invention and is suitable for receiving and storing lithium released from the cathode, and during the first charge / discharge cycle, the amount of lithium released is greater than the amount of lithium that would be released by the anode that has not been pre-lithiated according to the method of the present invention during the first charge / discharge cycle. Under certain conditions, as determined by a person skilled in the art in view of the teachings of the present application, any lithium from at least a portion to substantially all of the lithium from the pre-lithiated anode may be released when the battery undergoes the first charge / discharge cycle. The amount of lithium released from the pre-lithiated anode depends on the operating and processing conditions, as well as on the conditions of the lithium in the LixSiy alloy used during the pre-lithiation, for example, whether such lithium is active or inactive, which is well known to a person skilled in the art. In view of the teachings of this specification, a person skilled in the art can prepare a pre-lithiated anode that is suitable for releasing more lithium during the first charge / discharge cycle than the amount of lithium that would be released by the anode that has not been pre-lithiated according to the method of the present invention.
[0007] It is known that a variety of LixSiy alloys have been used in anode materials for lithium batteries. However, as an active material, the capacity of LixSiy decreases rapidly with cycling. In "Li-rich Li-Si alloys as lithium-containing negative electrode materials for high-energy lithium-ion batteries" by Iwamura et al., the following is stated: "The Shigematsu group has reported the first delithiation and lithiation capacities of 650 and 300 mAh g for Li21Si5. -1 -Li21Si5, and it dropped rapidly to 37 mAh g in the fourth cycle -1 -Li21Si5(Shigematsu's group has reported the first delithiation and lithiationcapacities of Li21Si5as 650and 300mAh g -1 -Li21Si5,and it quickly faded down to37mAh g -1 -Li21Si5 at the 4th cycle)”.
[0008] The inventors have found that micron-sized LixSiy molecules / particles are highly stable in a dry room and even in NMP (N-methyl-2-pyrrolidone), a commonly used solvent in the lithium-ion battery industry. In addition, such molecules / particles were found to be quite stable in humid air, more stable than expected. And such micron-sized LixSiy molecules / particles show unexpectedly high pre-lithiation efficiency. All of this is illustrated by the following discussion. BRIEF DESCRIPTION OF THE DRAWINGS
[0009] The present invention will be better understood by reference to the accompanying drawings, in which: Figure 1 shows the first cycle capacity of a button cell identified as Cell No. 1, which was pre-lithiated according to the present invention; Figure 2 shows the first cycle capacity of a button cell identified as Cell No. 2, which was pre-lithiated according to the present invention; Figure 3 shows the capacity of a button cell identified as an AA cell that was pre-lithiated according to the present invention; and Figure 4 is a graph providing data regarding the Coulombic efficiency ("CE") of button cells pre-lithiated in accordance with the present invention. DETAILED DESCRIPTION
[0010] In certain aspects of the invention described herein, the lithium content of at least one of the LixSiy alloys ranges from about 10 wt % to about 90 wt %. In certain aspects of the invention described herein, the lithium content of at least one of the LixSiy alloys ranges from about 10 wt % to about 70 wt %. In certain aspects of the invention described herein, the lithium content of at least one of the LixSiy alloys ranges from about 15 wt % to about 60 wt %. In certain aspects of the invention described herein, the lithium content of at least one of the LixSiy alloys ranges from about 40 wt % to about 50 wt %. By way of example only, and not to limit the invention, there are known LixSiy alloys with a lithium content of 19.8 wt % and known LixSiy alloys with a lithium content of 50.9 wt %, the lithium content of either of which would be suitable for the methods of the invention.
[0011] In certain aspects of the invention described herein, at least about 95% by volume of the plurality of particles have a size range of about 1 micron to about 200 microns. In other aspects, at least about 97% by volume, or at least about 99% by volume, or about 100% by volume of the plurality of particles have a size range of about 1 micron to about 200 microns. In certain aspects of the invention described herein, two or more particles have a size range of about 1 micron to about 50 microns.
[0012] In certain aspects of the invention described herein, at least one of the LixSiy alloys is coated. In certain aspects of the invention described herein, at least one of the LixSiy alloys is coated with an organic substance. In certain aspects of the invention described herein, at least one of the LixSiy alloys is coated with an inorganic substance.
[0013] As used herein, the terms "coated" and "surface treated" have the same meaning, i.e., the coated or surface treated LixSiy alloy has been in contact with or has been in contact with a substance that coats or surface treats the alloy, and optionally, subsequently treated, such as heat treated. Referring to Example 11, the LixSiy alloy is coated (surface treated) with an organic substance. Referring to Example 12, the LixSiy alloy is coated (surface treated) with an organic substance.
[0014] In certain aspects of the invention described herein, pre-lithiation of the electrode with the LixSiy alloy described herein is carried out in the presence of a solvent. Suitable solvents (including NMP) are known to those skilled in the art. In other aspects of the invention described herein, pre-lithiation of the electrode is carried out in the substantial absence of a solvent. As used herein, "substantially absent of a solvent" is meant to indicate that no solvent is intentionally introduced into the pre-lithiation process. In certain aspects of the invention described herein, the electrode is graphite-based or silicon-based. In certain aspects of the invention described herein, pre-lithiation of the electrode is carried out on at least a portion of at least one surface of the electrode. In certain aspects of the invention described herein, pre-lithiation of the electrode is carried out by combining one or more LixSiy alloys described herein with one or more conductive additives to form a combination and contacting at least a portion of the electrode with the combination. Suitable conductive additives are known to those skilled in the art and include, but are not limited to, carbon black. In certain aspects of the invention described herein, pre-lithiation of the electrode is carried out by combining one or more LixSiy alloys with conductive additives, binders, and optionally other suitable additives (as those skilled in the art are familiar with) to form a combination and contacting at least a portion of the electrode with the combination. In certain aspects of the invention described herein, pre-lithiation of the anode is performed by blending one or more LixSiy alloys with various additives, anode active materials, and solvents, and then coating them on a current collector to make an electrode. x Si y Any solvent in which the alloy is compatible, including NMP.
[0015] As is familiar to those skilled in the art, an electrode typically comprises a portion or layer called a "current collector" and a portion or layer comprising graphite, silicon, silicon oxide, or graphite with silicon and / or silicon oxide. For an anode, the current collector typically comprises copper. For a cathode, the current collector typically comprises aluminum. In certain aspects of the invention described herein, pre-lithiation of the electrode is performed by contacting one or more LixSiy alloys with one or more suitable substances comprising additives, active substances, or solvents, and then contacting the current collector with one or more LixSiy alloys. The current collector is then combined with a portion or layer comprising graphite, silicon, silicon oxide, or graphite with silicon and / or silicon oxide to form an electrode. The solvent can be any solvent suitable for use with a LixSiy alloy, such as NMP.
[0016] Various LixSiy alloys suitable for use in the invention described herein can be produced thermochemically or electrochemically. Depending on the reaction parameters, Li21Si5, Li4.7Si2, Li12Si7 and other such LixSiy alloys having different lithium contents can be formed. Moreover, these LixSiy alloys can be ground and sieved so that the resulting LixSiy alloy powders having certain desired particle sizes can be collected. These types of LixSiy alloys are available from companies such as Albemarle Corporation.
[0017] The electrode can be lithiated / pre-lithiated with the inventive LixSiy alloy particles described herein by any suitable method familiar to those skilled in the art, including those methods performed in the presence of a solvent and those methods performed substantially in the absence of a solvent. In this article, the terms "lithiation" and "pre-lithiation" are used interchangeably. Part to substantially all of the lithium from such a pre-lithiated electrode will be released during the first charge / discharge cycle of a battery containing an anode. The amount of released lithium depends on the operating and processing conditions, as well as the conditions of the lithium in the pre-lithiated LixSiy alloy, for example, whether such lithium is active or inactive, all of which are familiar to those skilled in the art. The amount of such released lithium will be sufficient to compensate for part to all of the inherent first cycle losses of lithium, mainly into graphite or silicon anodes. For example, the amount of lithium to be released from such a pre-lithiated anode is greater than the amount of lithium to be released from the same anode that has not been pre-lithiated according to the method of the present invention. As shown in the examples and related figures, the first cycle losses can be substantially completely compensated by the lithiation / pre-lithiation method of the present invention.
[0018] The pre-lithiation method as described herein is suitable for any electrode as is familiar to those skilled in the art, and is particularly suitable for graphite-based electrodes and silicon-based electrodes. Any such electrode may already contain some lithium. The pre-lithiation method as described herein is suitable for any anode and / or any cathode. Example
[0019] The following examples illustrate the principles of the present invention.It should be understood that the present invention is not limited to any one specific embodiment illustrated herein, whether in the examples or the remainder of this patent application.
[0020] Example 1. A lithium silicon alloy with a Li content of 44 wt% was ground by a rotor mill and sieved with a US standard sieve; and the powder between 80 mesh and 200 mesh was collected. The nominal sieve openings of the 80 mesh sieve and the 200 mesh sieve are 177 microns and 74 microns, respectively. About 1 gram of the resulting powder was transferred to a weighing bottle in a glove box filled with argon. The sealed weighing bottle was then transferred to a drying chamber with a dew point of -40°C. The sample was exposed to the air in the drying chamber, and the weight change of the sample over time was recorded, and any weight increase indicated a lithium reaction. After the first 6 hours, there was a negligible weight change (0.05%). Even after one day (24 hours), we measured a negligible weight change (-0.1%).
[0021] Example 2. (Comparative Example) About 1 gram of commercial lithium powder with a lithium content of >99% and a particle size of about 50 microns was transferred to a weighing bottle in a glove box filled with argon. The sealed weighing bottle was then transferred to a drying chamber with a dew point of -40°C. The sample was exposed to the air in the drying chamber and the weight change of the sample over time was recorded. We measured a 0.2% weight loss of the lithium powder, which was caused by the ability of this powder to be carried by air.
[0022] Example 3. About 0.6 grams of the same lithium-silicon powder used in Example 1 was transferred to a weighing bottle in a glove box filled with argon. The sealed weighing bottle was then transferred to a fume hood in a laboratory with ambient air. The temperature was recorded as 25° C. and the relative humidity was recorded as 55.6%. The sample was exposed to ambient air and no combustion was observed.
[0023] Example 4. Some of the same lithium silicon alloy powder used in Example 1 was sprinkled on a prefabricated graphite anode (graphite: conductive additive: binder 88:5:7, loading 4.7 mg / cm2 and porosity 40%) and then rolled with a rolling pin. The resulting anode was a graphite layer doped with LixSiy powder.
[0024] Example 5. A button cell identified as "cell 1" was assembled from the resulting anode of Example 4, with lithium foil as the counter electrode and 1M LiPF6 in 3 / 7EC / EMC (ethylene carbonate / ethyl methyl carbonate) as the electrolyte. The open circuit voltage (OCV) of the cell was measured to be about 0.46V. The cell was allowed to stand at OCV for 12 hours, and then the lithiation process (step 1) was started at C / 20 until the voltage reached 0.002V. The subsequent delithiation (step 2) was also carried out at C / 20 until the voltage reached 1.5V. Figure 1 The recorded specific capacities are plotted in , where the lithiation capacity is 412 mAh / g graphite and the delithiation capacity is 457 mAh / g graphite.
[0025] As shown in this example, the first cycle delithiation capacity was shown to be higher than the lithiation capacity, indicating that this LixSiy powder from Example 1 can be used as a pre-lithiation agent in lithium-ion batteries.
[0026] Example 6. A button cell identified as "cell 2" was also assembled from the resulting anode of Example 4, with lithium foil as the counter electrode and 1M LiPF6 in 3 / 7EC / EMC as the electrolyte, and tested. The results are shown in Figure 2 The OCV of cell No. 2 was recorded as 0.47 V, the lithiation capacity (see step 1) was recorded as 402 mAh / g graphite, and the delithiation capacity (see step 2) was recorded as 428 mAh / g graphite.
[0027] As shown in this example, the first cycle delithiation capacity was shown to be higher than the lithiation capacity, indicating that this LixSiy powder from Example 1 can be used as a pre-lithiation agent in lithium-ion batteries.
[0028] Example 7. A button cell identified as "cell 3" was assembled from the resulting anode of Example 4, with lithium foil as the counter electrode and 1M LiPF6 in 3 / 7EC / EMC as the electrolyte. The open circuit voltage (OCV) of the cell was measured to be about 0.47V. The cell was allowed to rest at OCV for 12 hours, and then the delithiation process (step 1) was started at C / 20 until the voltage reached 1.5V. Figure 3 As shown in , for cell 3, this initial delithiation capacity was recorded as 48.9 mAh / g graphite. (By comparison, for a typical graphite anode that has not undergone any prelithiation, since there is no lithium in it, its initial delithiation capacity would be close to zero if tested with an initial delithiation step.) Figure 3 As shown in , the No. 3 cell (step 2) is then lithiated at C / 20 until the voltage reaches 0.002 V. The subsequent delithiation (step 3) is also performed at C / 20 until the voltage reaches 1.5 V. Figure 3The recorded specific capacities are plotted in , where the lithiation capacity is 450 mAh / g graphite and the delithiation capacity is 406 mAh / g graphite.
[0029] As shown in this example, a cell having a graphite layer doped with the LixSiy powder from Example 1 exhibited a delithiation capacity of 48.9 mAh / g without any lithiation cycles, demonstrating that this LixSiy powder can be used as a pre-lithiation agent in lithium-ion batteries.
[0030] Example 8. After the initial C / 20 cycle, the button cell identified as cell No. 1 of Example 7 was cycled 3 more times at C / 10. The coulombic efficiency (CE) was calculated according to Equation 1 [CE = delithiation capacity / lithiation capacity * 100%]. Figure 4 As shown in , the initial CE was above 100%, and the CE for the remaining cycles was 99%.
[0031] Example 9. A lithium silicon alloy having a Li content of 44 wt% was ground by a centrifugal grinder and sieved with a US standard sieve; and powders smaller than 325 mesh were collected. The nominal opening of the 325 mesh sieve is 44 microns. About 1 gram of the resulting powder was transferred to a weighing bottle in an argon-filled glove box, and after the first 7 hours, the weight gain in the drying chamber (dew point of -41.4°C) was recorded as 0.7%.
[0032] Example 10(a). In a glove box filled with argon, 14.015 grams of lithium rod pieces and 11.022 grams of silicon chips were placed in a tantalum crucible to obtain a target lithium silicon alloy with a lithium content of 56.0 weight %. The crucible was then placed in an oven in the glove box and heated to 750°C, stirred, and reheated for 1 hour. The resulting alloy was poured into a cooling tray. Once cooled to room temperature, the alloy was crushed with a hammer and then transferred to a ball mill. A 10mm stainless steel ball was used in a ball mill to grind the material for different time periods at 100rpm, 300rpm, and 400rpm. The alloy flakes after grinding were not broken, but large, depressed agglomerates, which indicated that the material was too soft to be ground into powder.
[0033] Example 10(b). In a glove box filled with argon, 5.718 grams of lithium rod pieces and 19.245 grams of silicon chips were placed in a tantalum crucible to obtain a target lithium silicon alloy with a lithium content of 22.9% by weight. The crucible was then placed in an oven inside the glove box and heated to 700°C, stirred, and heated for another hour. The resulting alloy was poured into a cooling tray. Once cooled to room temperature, the alloy was crushed with a hammer and then transferred to a ball mill. The material was ground at 100 rpm for 1 hour using a 3 mm stainless steel ball in a ball mill, and then ground at 300 rpm for 30 minutes. The resulting powder material was sieved with a US standard sieve; and the powder passing through a 325 mesh sieve was collected.
[0034] The actual lithium content of the obtained material was 22.3 wt % as determined by acid titration. XRD (X-ray diffraction) confirmed that the obtained material contained Li 12 Si7.
[0035] About 1 gram of the resulting powder was transferred to a weighing bottle in an argon-filled glove box and a weight gain of 0.7% was recorded in a drying chamber (dew point -41.4°C) after the first 7 hours.
[0036] Some screened lithium silicon alloy powder was sprinkled on a prefabricated graphite anode (graphite: conductive additive: binder 88:5:7, loading of 7.1 mg / cm2 and porosity of 40%) and then rolled with a doctor blade, and the loading of the LixSiy powder was measured to be about 1.05 mg / cm2.
[0037] Five button cells were assembled from the resulting anodes with lithium foil as the counter electrode and 1M LiPF6 in 3 / 7 EC / EMC as the electrolyte. The open circuit voltage (OCV) of the cells was measured to be about 0.597V to 0.634V. The cells were left at OCV for 12 hours and then the delithiation process was started at C / 20 until the voltage reached 1.5V. The average initial delithiation capacity was recorded as 37.8mAh / g graphite.
[0038] Example 11. Under argon atmosphere, in a glass flask, a portion (15 grams) of the lithium silicon alloy powder of Example 9 (having 44% lithium and sieved through a 325 mesh screen) was mixed with 33.2 mL of a 2% LiBOB solution (LiBOB = lithium bis(oxalato)borate) in anhydrous PC / DMC (1:1 wt / wt; PC = propylene carbonate; DMC = dimethyl carbonate) and stirred at room temperature for 2 hours. The resulting suspension was filtered in the absence of air, dried under vacuum at room temperature, and dried again under vacuum after heating to 200° C. After sieving through a 325 mesh screen, 12 grams of gray powder were collected. A new exotherm can be observed in the DSC of the treated lithium silicon alloy, which is absent in the untreated lithium silicon alloy.
[0039] About 1 gram of the resulting LiBOB-treated powder was transferred to a weighing bottle in an argon-filled glove box, and negligible weight gain (-0.06 wt%) was recorded in the dry room (dew point -42.6 °C) after the first 7 hours.
[0040] Some of the sieved LiBOB-treated lithium-silicon alloy powder was sprinkled on a prefabricated graphite anode (graphite: conductive additive: binder 88:5:7, loading 7.1 mg / cm 2 The porosity was 40%), and then the surface was rolled with a scraper. The loading of lithium silicon powder was measured to be about 1.05 mg / cm 2 .
[0041] Five button cells were assembled from the resulting anodes with lithium foil as the counter electrode and 1M LiPF6 in 3 / 7 EC / EMC as the electrolyte. The open circuit voltage (OCV) of the cells was measured to be about 0.460V to 0.467V. The cells were left at OCV for 12 hours and then the delithiation process was started at C / 20 until the voltage reached 1.5V. The average initial delithiation capacity was recorded as 64.1mAh / g graphite.
[0042] Example 12. A lithium silicon alloy having a Li content of 44 wt% was ground by a centrifugal grinder and sieved with a US standard sieve; and powders smaller than 325 mesh were collected. The nominal mesh opening of the 325 mesh sieve is 45 microns. About 10 grams of the resulting powder was transferred to a stainless steel crucible. A 4 wt% solution of polyisobutylene (PIB; average molecular weight of about 1,000,000) in hexane was added until all the powder was wetted. A solution of about 6 grams of PIB in hexane was used. The alloy and polymer solutions were stirred until uniform. The crucible was then placed in an oven in an argon glove box and heated to 600°C. The oven was kept at 600°C for 3 hours, then the crucible was removed and allowed to cool to room temperature.
[0043] About 1 gram of the resulting powder was transferred to a weighing bottle in an argon-filled glove box and a weight gain of 0.5% was recorded in a drying chamber (dew point -42.6°C) after the first 8 hours.
[0044] Example 13. In a drying chamber, a portion (5.0 grams) of the lithium silicon alloy powder from Example 9, which had 44% lithium and particles sieved through a 325 mesh screen, was made into a slurry having the following formulation: -97% lithium silicon alloy powder -2% PIB binder -1% conductive additive - Hexane as solvent - Solids content is about 37.5% A prefabricated graphite anode (graphite:conductive additive:binder 88:5:7, loading 7.1 mg / cm2 and porosity 40%) was contacted with the resulting slurry using a scraper on a slide. After air drying, the resulting anode comprised graphite with a surface layer containing 97% lithium silicon alloy.
[0045] Five button cells were assembled from air-dried anodes with lithium foil as counter electrode and 1M LiPF6 in 3 / 7EC / EMC as electrolyte. The open circuit voltage (OCV) of the cell was measured to be about 0.4V. The cell was left at OCV for 12 hours and then the delithiation process was started at C / 20 until the voltage reached 1.5V. The average initial delithiation capacity was recorded to be 90mAh / g graphite.
[0046] Example 14. In a drying chamber, a portion (5.0 grams) of the lithium silicon alloy powder from Example 9, which had 44% lithium and particles sieved through a 325 mesh screen, was made into a slurry having the following formulation: -97% lithium silicon alloy powder -2% PVDF (polyvinylidene (di) fluoride) adhesive -1% conductive additive - Hexane as solvent - Solids content is about 43.4% A prefabricated graphite anode (graphite: conductive additive: binder 88:5:7, loading 7.1 mg / cm2 and porosity 40%) was contacted with the resulting slurry using a doctor blade on a slide, and then dried in a vacuum oven at 50° C. for 20 minutes. The resulting anode included graphite with a surface layer containing 97% lithium silicon alloy.
[0047] Two coin cells were assembled from oven dried anodes with lithium foil as counter electrode and 1M LiPF6 in 3 / 7EC / EMC as electrolyte. The open circuit voltage (OCV) of the cell was measured to be about 0.470V.
[0048] advantage An advantage of the present invention is that certain Li alloys are more stable than Li itself. For example, LixSiy alloy powders with a Li content of about 10-90 wt% are stable for more than 24 hours in a dry room and are quite stable in humid air; and are easier to handle than Li itself, which makes the application and commissioning process easier when applied to an electrode.
[0049] Although the present invention has been described in terms of one or more preferred embodiments, it should be understood that other modifications may be made without departing from the scope of the invention as set forth in the following claims.
Claims
1. A method for pre-lithiation of an electrode, the electrode consisting of a current collector and an active material layer disposed thereon, the active material layer forming the surface of the electrode, the method comprising contacting the current collector with a plurality of particles of one or more LixSiy alloys for pre-lithiation, and then combining the current collector with the active material layer to form an electrode, the plurality of particles being substantially in powder form in the absence of a solvent, wherein at least 95% by volume of the particles have a size range of 1 micron to 70 microns, and each of the LixSiy alloys contains lithium, and the lithium content of at least one of the LixSiy alloys ranges from 15 wt% to 60 wt%, wherein the contacting of the electrode is performed on the current collector of the electrode, and wherein the active material is selected from the group consisting of graphite, silicon, silicon oxide, and graphite with silicon and / or silicon oxide.
2. The method of claim 1, wherein the lithium content of at least one of the LixSiy alloys ranges from 10 wt% to 70 wt%.
3. The method of claim 1, wherein the lithium content of at least one of the LixSiy alloys ranges from 15 wt% to 60 wt%.
4. The method of claim 1, wherein the lithium content of at least one of the LixSiy alloys ranges from 40 wt% to 50 wt%.
5. The method of claim 1, wherein two or more of the particles have a size ranging from 1 micron to 150 microns.
6. The method of claim 1, wherein at least 95% by volume of the particles are in the size range of 1 micron to 50 microns.
7. The method of claim 1, wherein at least 97% by volume of the particles are in the size range of 1 micron to 70 microns.
8. The method of claim 1, wherein at least one of the LixSiy alloys has been contacted with an organic substance.
9. The method of claim 1, wherein at least one of the LixSiy alloys has been contacted with an organic substance, wherein the organic substance comprises boron.
10. The method of claim 1, wherein at least one of the LixSiy alloys has been contacted with an organic substance, wherein the organic substance comprises boron and oxygen.
11. The method of claim 1, wherein at least one of the LixSiy alloys has been contacted with an organic substance, wherein the organic substance comprises lithium bis(oxalato)borate.
12. The method of claim 1, wherein at least one of the LixSiy alloys has been contacted with an inorganic substance.
13. The method of claim 1, wherein the electrode is a graphite-based electrode or a silicon-based electrode.
14. An electrode pre-lithiated according to the method of claim 1.
15. A secondary battery comprising the electrode according to claim 14.
16. The battery of claim 15, wherein the electrode is an anode.
17. The battery of claim 16, wherein the anode is adapted to release a greater amount of lithium when the battery undergoes a first charge / discharge cycle than would be released by an anode that has not been pre-lithiated according to the method of claim 1.